HeadBox: A Facial Blendshape Animation Toolkit for the Microsoft Rocketbox Library - Archer, Kelsey; Ofek, Eyal; Jakubzak, Ken; Bruner, Shawn; Gonzalez Franco, Mar (IEEE VR 2022, 2022)
HeadBox is a series of opensource tools to do facial animation on the Microsoft Rocketbox avatar library. It includes a tool to create blendshapes out of the facial bones inside Maya and transfer the new blendshapes to the other avatars in the library. We have created a total of 15 visemes, 48 FACS, 30 for the Vive facial tracker. These blendshapes have been released with the original library. An additional Unity demo shows the use these tools with Openface and Oculus Lipsync.